Comparing the Effectiveness of Mindfulness and Positive Psychology Training on Reappraisal and Suppression in Students with Generalized Anxiety Disorder Symptoms - Nasiri Karbasdehi, Zahra; Fakhri, Mohammadkazem; Ghanadzadegan, Hosseinali (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of this study was to compare the effectiveness of mindfulness and positive psychology training on reappraisal and suppression in students with generalized anxiety disorder symptoms.Methods and Materials: This was a quasi-experimental study with a pre-test, post-test, three-group design, and a three-month follow-up period. The population of this research consisted of female high school students in Tehran with generalized anxiety disorder symptoms. A total of 45 students with generalized anxiety disorder symptoms were selected through a multi-stage cluster sampling method and purposeful sampling based on the scores obtained from the Spitzer et al. (2006) scale and randomly assigned to three groups (two experimental groups and one control group). All three groups completed the Gross and John (2003) Emotion Regulation Questionnaire. The first group received mindfulness training, the second group received positive psychology training in eight sessions of 1.5 hours each, and the control group did not receive any treatment. The data were analyzed using repeated measures analysis of variance and follow-up LSD test.Findings: The findings indicated that there was no significant difference between the effects of mindfulness and positive psychology training on reappraisal and suppression (p>0.5).Conclusion: Based on the results, in students with generalized anxiety disorder symptoms, both mindfulness and positive psychology training were beneficial.